The Start Matters: A Comparative Analysis of Climate Equity Among UNFCCC Country Parties and Country Groups - Liu, Zhe (2024)
Incorrect indicators and starting years for emission cumulation can lead to confusion regarding the concepts of climate equity and climate responsibility. This article examines the variations in the results obtained by using different indicators and starting years to calculate climate equity and climate responsibilities among country parties and country groups of the UNFCCC. The article utilizes historical greenhouse gas (GHG) emissions data from 193 countries spanning the period 1850 to 2021. The data is aggregated from various sources including EDGAR, Climate Watch, and Global Carbon Budget (GCB). The article calculates cumulative GHG emissions and cumulative GHG emissions per capita, with starting years 1850, 1970, and 1990. By highlighting differences in various indicators, the article aims to provide a better understanding of climate responsibilities, climate beneficiaries, and climate equity. The results demonstrate that cumulative emissions and cumulative emissions per capita are scientific indicators that reveal a country’s level of climate responsibility and climate equity. Negotiators can achieve consensus more easily in the complex system if they have a comprehensive and scientific understanding of climate equity. It is suggested that country groups under the UNFCCC use scientific indicators and methodologies to reveal climate responsibilities and climate equity.